Divergence and convergence of salient stakeholders' perceptions toward forensic accounting education: importance, obstacles and pedagogies - Rahaf Ibrahim Alkhalaileh; Hashem Alshurafat; Huthaifa Al-Hazaima (Journal of Business and Socio-Economic Development, 2024)
Purpose – This research study aims to identify barriers to incorporating forensic accounting into accounting curricula in Jordanian universities. The study examines the differences in perspectives among various accounting education stakeholders, including students, educators and accounting and auditing employees/managers, on forensic accounting education. Design/methodology/approach – The research methodology is quantitative and involves administering a survey questionnaire. The data obtained are analyzed using techniques including t-test analysis, one-way ANOVA and post-hoc. Findings – The study reveals that educators have a more favorable view toward incorporating forensic accounting into university accounting curricula in Jordan, while accountants and auditors (employees/managers) are more strongly convinced of its importance. Furthermore, the biggest challenge to integrating forensic accounting, as perceived by stakeholders, is the lack of related job opportunities. Practical implications – The study significantly contributes to accounting education research by providing valuable information on barriers to incorporating forensic accounting into the accounting curricula of Jordanian educational institutions from the perceptive of various stakeholders. Therefore, this study may assist educators in overcoming obstacles in offering forensic accounting education. Originality/value – The study carries important implications for the inclusion of forensic accounting in the accounting curricula of Jordanian educational institutions. By comprehending the different viewpoints of various stakeholders, educators and policymakers can address recognized challenges and strive for the effective integration of forensic accounting in accounting curricula. As a result, accounting students will receive a more comprehensive education, and graduates will be better equipped for successful careers in the field.